Konstruksi Makna Pendidikan Formal dan Madrasah Diniyah di Kalangan Santri: Studi Kasus di Pondok Pesantren Miftahul Ulum Ranupakis - Nining Winarsih; Mumtaza Khoirotul Magfiroh (PT. Citra Media Publishing, 2026)
The low interest of students (santri) in formal schooling and their strong enthusiasm for madrasah diniyah has become a long-standing pattern at Miftahul Ulum Ranupakis Islamic Boarding School. This phenomenon reflects differing perceptions among students toward the two educational systems they simultaneously experience. This study aims to explore the meaning of formal schooling and madrasah diniyah from the students’ perspective using a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that formal schooling is mainly perceived as a means to obtain academic certification, while madrasah diniyah is regarded as the core of pesantren education that instills religious knowledge, moral values, and religious identity. These results highlight the central role of madrasah diniyah in shaping students’ educational meaning-making, while formal schooling is positioned as a complementary component. The study recommends stronger synergy between formal schooling and madrasah diniyah so that both systems can mutually reinforce the holistic development of students’ character and competencies.